2017
DOI: 10.18632/oncotarget.22958
|View full text |Cite
|
Sign up to set email alerts
|

FRK inhibits breast cancer cell migration and invasion by suppressing epithelial-mesenchymal transition

Abstract: The human fyn-related kinase (FRK) is a non-receptor tyrosine kinase known to have tumor suppressor activity in breast cancer cells. However, its mechanism of action has not been fully characterized. We generated FRK-stable MDA-MB-231 breast cancer cell lines and analyzed the effect on cell proliferation, migration, and invasiveness. We also used kinome analysis to identify potential FRK-regulated signaling pathways. We employed both immunoblotting and RT-PCR to identify/validate FRK-regulated targets (protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Interestingly, overexpression of SMAD4 restores the BRK-induced suppression of FRK level in the TNBC cells stably expressing BRK. Previous studies have shown that the expression of SNAIL is upregulated in FRK-knocked down breast cancer cells (30). We observed that activated BRK induces SLUG and SNAIL expression, while overexpression of FRK significantly suppresses the mesenchymal marker SLUG, suggesting an FRK-dependent mechanism for BRK induced promotion of EMT.…”
Section: Discussionsupporting
confidence: 51%
“…Interestingly, overexpression of SMAD4 restores the BRK-induced suppression of FRK level in the TNBC cells stably expressing BRK. Previous studies have shown that the expression of SNAIL is upregulated in FRK-knocked down breast cancer cells (30). We observed that activated BRK induces SLUG and SNAIL expression, while overexpression of FRK significantly suppresses the mesenchymal marker SLUG, suggesting an FRK-dependent mechanism for BRK induced promotion of EMT.…”
Section: Discussionsupporting
confidence: 51%
“…Of the 12 genes that were downregulated by TRIM44, three genes were found to possess tumor suppressive functions (Figure A; FRK, EGR1 and BCL2L14 ). We then used the Oncomine dataset to analyze the expression level of these three genes in tumors. FRK was the only gene that showed low expression levels in cancer compared with benign tissues (Figures B,C and ).…”
Section: Resultsmentioning
confidence: 99%
“…This mutation of the tyrosine residue seemed to prevent the NEDD4‐1 mediated ubiquitination of PTEN . Another study revealed that FRK inhibited cell migration of breast cancer cells through suppressing EMT . FRK is also involved in large cell lymphoma and glioma as a tumor suppressor .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations